Comparing three lenses of policy choice. - Zahariadis, Nikolaos (Policy Studies Journal)
This paper compares three lenses that explain policy choice. They include rational choice, advocacy coalitions, and multiple streams. The argument is that the three lenses generate complementary rather than competing explanations of the same event. Complementary lenses are those that are not applicable under the same conditions. Applicability of each lens is established by examining actor goals and environmental structure and by exploring predictive capability and descriptive accuracy. Finally, the paper charts a research agenda designed to make the lenses more directly competing. Reprinted by permission of the publisher.